The Role of Creativity and Self-Directed Learning in Enhancing Students’ Problem-Solving Skills (A Systematic Literature Review from 2019 to 2024) - Viki Marta Tifani; Yoto Yoto; Widiyanti Widiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to systematically analyze the role of creativity and self-directed learning in enhancing students’ problem-solving skills in Informatics learning at Vocational High Schools. This review used a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 Statement. A total of 17 academic articles published between 2019 and 2024 were selected from several databases, including Scopus, ERIC, DOAJ, and Google Scholar. The analysis results indicated that creativity and self-directed learning had a strong and complementary relationship in shaping students’ critical and adaptive thinking abilities. Creativity contributed to generating new ideas and innovative solutions, while self-directed learning strengthened responsibility, self-reflection, and the ability to regulate the learning process. These two factors have been proven to contribute positively to the improvement of problem-solving skills, particularly in the contexts of project-based and problem-based learning and digital literacy. These findings affirm that Informatics learning in Vocational High Schools should be guided by pedagogical models that foster creativity and self-direction, and that are oriented toward problem-solving, as part of developing 21st-century competencies